The Inflammatory Milieu of Eosinophilic Esophagitis: A Contemporary Review With Emphasis in Putative Immunohistochemistry and Serologic Markers. Issue 7 (August 2018) - Lepe, Marcos; O'Connell, David; Lombardo, Kara A.; Herzlinger, Michael; Mangray, Shamlal; Resnick, Murray B.; Matoso, Andres
Abstract : Eosinophilic esophagitis is a chronic disease characterized by esophageal dysfunction, frequent clinical history of atopy, and eosinophilic inflammation of the esophagus. Within the esophageal mucosa, there is a wide variety of immune mediators, chemotactic factors, mediators of transcription, and markers of epithelial differentiation and integrity that are overexpressed or underexpressed in eosinophilic esophagitis, offering many candidates for biomarkers with diagnostic or prognostic potential. In this review, we summarize the results from studies performed so far to evaluate the detection of these markers by immunohistochemistry on esophageal biopsies. In addition, we briefly describe some attempts to identify markers that could be detected in serum to be used to diagnose or monitor the disease without the need of a biopsy.